Addressing knowledge gaps in rice growing in eastern uganda - Van Campenhout, Bjorn; Walukano, Wilberforce; Van Asten, Piet (International Food Policy Research Institute, 2016)
Rice is becoming increasingly important for Ugandan farm households, both as a cash crop and staple food. Rice production in Uganda increased from about 110,000 tons in 2000 to about 237,000 tons in 2014 and the share of rice in total consumption also grew over time. Previous research as part of the PASIC project, a policy action project funded by the Embassy of the King-dom of the Netherlands in Uganda and led by the Ministry of Agriculture, Animal Industries and Fisheries (MAAIF) with support of IFPRI, the International Institute of Tropical Agriculture (IITA), and the Economic Policy Research Centre (EPRC), suggests that a lack of knowledge may be an important constraint to sustainable intensification among rice growers in eastern Uganda. In-deed, rice growing is a complex activity that requires substantial technical and managerial know-how. Successful rice growing involves a range of activities, such as leveling of fields, construction of bunds and canals, sowing in nurseries, transplanting, water and nutrient management, threshing, drying, winnowing, and milling. To get high yields, all of these activities need to be performed according to recommended practices and at particular points in time. In addition, rice growing involves complex inter-temporal decision making, where money and labor invested today needs to be compared to uncertain earnings in the fu-ture. Hence, farmers need to be informed about, for instance, the cost of fertilizer and the expected return to its use on rice, or about the expected benefits of investing time in field preparation.